Correlation between water salinity and arterial hypertension - Branco, Ana Emília Castelo; Assunção, Joyce Luise Sabá; Colares Filho, George; Bassi, Daniela; Silva, Fabricio Brito (Ciência e Natura, 2018)
Hypertension is the main risk factor for the development of cardiovascular diseases. The objective of this study was to evaluate the correlation between cases of hypertension and environmental aspects related to water salinity in the municipality of Arari-Maranhão. The following data were evaluated: 1) secondary data on cases of hypertension reported from 2002 to 2012 registered in the Hiperdia Program of the Department of Informatics of SUS (DATASUS), in the municipality of Arari-Maranhão; 2) a temporal series of climatic data and river water quality measured by the physicochemical parameters and the water flow of the Mearim River; and 3) the statistical correlation between the indicators of water quality and the cases of hypertension of the study sample. The results revealed a seasonality in cases of hypertension in the municipality of Arari. This variation was inversely related to the precipitation and the salinity of the river water. Thus, decreased precipitation resulted in increase driver salinity and, consequently, increased consumption of salt by the population, increasing the number of cases of hypertension. The correlation between cases of hypertension and precipitation or salinity was significant and negative. These results revealed a significant correlation between cases of hypertension, water quality, and climatic factors.